Comparative Analysis of Clinical Parameters and Sputum Biomarkers in Establishing the Relevance of Filamentous Fungi in Cystic Fibrosis - Patel, Deepa; Dacanay, Keith Chester; Pashley, Catherine H.; Gaillard, Erol A. (Frontiers in Cellular and Infection Microbiology, 2021)
Background The relationship between fungal culture (FC) positivity and airway inflammation in CF is largely unknown. Identifying the clinical significance of filamentous fungi in CF using both clinical parameters and biomarkers may change our antimicrobial therapeutic strategies. Objectives To investigate the clinical characteristics and airway biomarker profile in relation to the detection of filamentous fungi in respiratory samples obtained from CF patients. Methods A prospective cohort study over 24 months, including children and adults with CF. Participants provided sputum and/or bronchoalveolar lavage samples, which underwent processing for bacterial and fungal culture, leukocyte differential cell count and biomarker analysis for neutrophil elastase (NE), interleukin-8 (IL-8), galactomannan and tumor necrosis factor receptor type 2 (TNF-R2). We performed FC using neat sputum plugs, an approach shown to be more sensitive compared to routine laboratory testing. Results Sixty-one patients provided 76 respiratory samples (72 sputum and 4 BAL). Median age was 17 years (range 6 months–59 years). FC positivity was noted in 49% of the cohort. FC positivity was greater during pulmonary exacerbation compared to the stable state (67 versus 50%). Participants aged 5–30 years had a lower FEV1 within the FC positive group. A significant association between FC positivity and non-tuberculosis mycobacterial (NTM) culture was observed on non-parametric testing (p = 0.022) and regression analysis (p = 0.007). Exposure to indoor mold was a predictor for FC positivity (p = 0.047). There was a trend towards increased lung clearance index (LCI), bronchiectasis and intravenous antibiotic use in the FC positive group. There was no significant difference in biomarkers between FC positive and negative patients. Conclusion Aspergillus. fumigatus is the commonest filamentous fungi cultured from CF airways. We found no difference in the airway biomarker profile between FC positive and negative patients. The role of galactomannan and TNFR2 as fungal specific biomarkers in CF remains uncertain. FC positivity is associated with a lower FEV1 in younger patients, a lower LCI, NTM positivity, bronchiectasis, and intravenous antibiotic exposure. Larger trials are needed to determine the role of galactomannan and TNF-R2 as potential fungal biomarkers in CF.